Contemporary technological development and challenges to the international humanitarian law - Islam, Mohammad Saidul (IIUC Studies, 2018)
International Humanitarian Law (IHL), is an important branch of the public international law, it does not speak about the lawfulness of armed conflict, it seeks instead to protect the civilians and hors de combats through imposing limitation to the freedom of the choice of the weapons and strategies of warfare. The development of science and technology has significantly changed the nature of weapons and war strategies and complicated the implementation of IHL. This article describes the technologically developed new weapons and methods which are randomly used in the contemporary armed conflict. This paper also focuses on the new challenges faced by the frequent use of technologically advanced weapons in the modern armed conflict. IIUC Studies Vol.13 December 2016: 53-68